(–)-Epicatechin Modulates Mitochondrial Redox in Vascular Cell Models of Oxidative Stress. (9th June 2020) - Keller, Amy; Hull, Sara E.; Elajaili, Hanan; Johnston, Aspen; Knaub, Leslie A.; Chun, Ji Hye; Walker, Lori; Nozik-Grayck, Eva; Reusch, Jane E. B.
Abstract : Diabetes mellitus affects 451 million people worldwide, and people with diabetes are 3-5 times more likely to develop cardiovascular disease. In vascular tissue, mitochondrial function is important for vasoreactivity. Diabetes-mediated generation of excess reactive oxygen species (ROS) may contribute to vascular dysfunction via damage to mitochondria and regulation of endothelial nitric oxide synthase (eNOS). We have identified (–)-epicatechin (EPICAT), a plant compound and known vasodilator, as a potential therapy. We hypothesized that mitochondrial ROS in cells treated with antimycin A (AA, a compound targeting mitochondrial complex III) or high glucose (HG, global perturbation) could be normalized by EPICAT, and correlate with improved mitochondrial dynamics and cellular signaling. Human umbilical vein endothelial cells (HUVEC) were treated with HG, AA, and/or 0.1 or 1.0  μ M of EPICAT. Mitochondrial and cellular superoxide, mitochondrial respiration, and cellular signaling upstream of mitochondrial function were assessed. EPICAT at 1.0  μ M significantly attenuated mitochondrial superoxide in HG-treated cells. At 0.1  μ M, EPICAT nonsignificantly increased mitochondrial respiration, agreeing with previous reports. EPICAT significantly increased complex I expression in AA-treated cells, and 1.0  μ M EPICAT significantly decreased mitochondrial complex V expression in HG-treated cells. No significant effects were seen on either AMPK or eNOS expression. Our study suggests that EPICAT is useful in mitigating moderate ROS concentrations from a global perturbation and may modulate mitochondrial complex activity. Our data illustrate that EPICAT acts in the cell in a dose-dependent manner, demonstrating hormesis.